Multimodal MRI of Nonhuman Primate Stroke - Wey, Hsiao-Ying (Transl Stroke Res, 2012)
Stroke is the fourth leading cause of death. Despite decades of research, no neuroprotective drug has proven to be effective clinically. One widely accepted view to account for this negative outcome is that the rodent stroke model simply does not adequately reflect the complexity of human stroke. Recent failures of several high-profile neuroprotective drugs for stroke treatment in phase III clinical trials further underscore the importance of developing adequate animal models for stroke research. The brain organization and vascular circuitry of nonhuman primates (NHPs) are more homologous with humans than the widely used rodent for stroke modeling. The Stroke Therapy Academic Industry Roundtable, a national committee commissioned by the American Heart Association, recommended that clinically relevant NHP stroke models be established for developing and assessing neuroprotective drugs. The aim of this article is to review the challenges and applications of magnetic resonance imaging studies of NHP stroke models.